Redistributive Taxation, Inequality, and Intergenerational Mobility - Andrea Schneider (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2007)
Education decisions determine a great part of future income. This paper argues that if education is financed by parents' current income a lump-sum tax reduces inequality if all parents have strict investment incentives. However, if some parents are indifferent there is a possible decrease in the wage gap via a contrary indirect tax effect which drops the returns of schooling. Under strict incentives social mobility is not affected, but it increases if skilled parents have weak incentives and decreases if unskilled parents are indifferent in their investment decision.
urn:nbn:de:gbv:705-opus-17026
Keywords: H23; H31; D31; D91; I21; J24; J62; 330; Intergenerational mobility; Inequality; Redistribution; Lumpsum tax; Soziale Mobilität; Generationenbeziehungen; Bildungsinvestition; Einkommensumverteilung; Kopfsteuer; Einkommensverteilung; Theorie